2004
DOI: 10.1073/pnas.0401104101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a domain within the multifunctional Vibrio cholerae RTX toxin that covalently cross-links actin

Abstract: The Gram-negative pathogen Vibrio cholerae causes diarrheal disease through the export of enterotoxins. The V. cholerae RTX toxin was previously identified and characterized by its ability to round human laryngeal epithelial (HEp-2) cells. Further investigation determined that cell rounding is caused by the depolymerization of actin stress fibers, through the unique mechanism of covalent actin cross-linking. In this study, we identify a domain within the full-length RTX toxin that is capable of mediating the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 18 publications
1
142
1
1
Order By: Relevance
“…By analogy to T3SS and T4SS (21,22), the extracellular secretion of Hcp, VgrG-1, and VgrG-2 may actually reflect a more complex process that involves the translocation of these proteins by V. cholerae into eukaryotic target cells. Recently, Sheahan et al (23) reported that VgrG-1 and the V. cholerae RtxA toxin share a subdomain that mediates actin covalent crosslinking and cytotoxicity when expressed in the cytosol of mammalian cells. The extracellular cytotoxin RtxA, however, is not required for Dictyostelium virulence, because a rtxA mutant of V52 still kills amoebae (data not shown).…”
Section: Cholerae Uses the Vas Pathway To Mediate Virulence Towardmentioning
confidence: 99%
“…By analogy to T3SS and T4SS (21,22), the extracellular secretion of Hcp, VgrG-1, and VgrG-2 may actually reflect a more complex process that involves the translocation of these proteins by V. cholerae into eukaryotic target cells. Recently, Sheahan et al (23) reported that VgrG-1 and the V. cholerae RtxA toxin share a subdomain that mediates actin covalent crosslinking and cytotoxicity when expressed in the cytosol of mammalian cells. The extracellular cytotoxin RtxA, however, is not required for Dictyostelium virulence, because a rtxA mutant of V52 still kills amoebae (data not shown).…”
Section: Cholerae Uses the Vas Pathway To Mediate Virulence Towardmentioning
confidence: 99%
“…Although all VgrG proteins are related to each other through several conserved domains (see below), VgrG-1 is unique in that it carries a C-terminal extension of 446-aa residues that shares extensive homology to the actin cross-linking domain (ACD) of the V. cholerae RtxA toxin (25) [see supporting information (SI) Fig. 6].…”
Section: Secretion Of Hcp Requiresmentioning
confidence: 99%
“…6]. Indeed, ectopic expression of the ACD from VgrG-1 inside eukaryotic cells was reported to cause cell rounding and covalent cross-linking of actin (25).…”
Section: Secretion Of Hcp Requiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the V. cholerae rtxA toxin has been recognized as one the most potent cytotoxic toxins, which display actin cross-linking activities and are secreted to the bacterial exterior by the type I secretion systems (TISS) consisting of rtxB, rtxD and rtxE (14,20,21). Another group has shown V. vulnificus RTX toxin to be a multifunctional cytotoxin, which performs a central role in the pathogenesis of V. vulni ficus infectious disease.…”
Section: Comparative Analysis Of Proteins In the Culture Supernatantsmentioning
confidence: 99%